Analysis Difficulty of Mathematical Creative Thinking Ability Reviewed From Learning Styles Through Problem Based Learning - Sirait, Asril Rais (Advances in Social Sciences Research Journal, 2018)
This study aims to analysis and find out: (1) level the MCTA reviewed from learning styles through problem based learning; (2) difficulties experienced by students in solving the problem of MCTA reviewed from learning styles through problem based learning. This research is qualitative research. The subjects of this study were students of SMP Negeri 42 Medan class VIII-A which amounted to 35 students. The research instrument used tests of mathematical creative thinking ability, Kolb’s learning style questionnaires, and interviews. The results of the study are as follows: (1) the level of MCTA for learning styles of accommodation 2 students (moderate), and 5 students (low); the level of MCTA for divergent learning styles 2 students (high), 4 students (moderate), and 7 students (low); the level of MCTA for assimilation learning styles 3 students (moderate), and 7 students (low); the level of MCTA for convergent learning styles 1 students (high), 2 students (moderate), and 2 students (low). (2) students with accommodation learning styles experience difficulties in aspects concepts, procedures and principles; students with divergent learning styles experience difficulties in aspects facts, concepts, procedures, and principles; students with assimilation learning styles experience difficulties in aspects facts, procedures, and principles; students with convergent learning styles experience difficulties in aspects facts, concepts, procedures and principles.